Comparison of multiple intelligence fields of physical education and sports college students - Didem Kemec (Selcuk University, 2016)
Aim of this study was to identify and compare the areas of multiple intelligence of School of Physical Education and Sports students according to some parameters. Research group consists of 185 people, chosen randomly, who studied at Sakarya and Gaziantep University School of Physical Education and Sports during the academic year of 2014-2015. In this research "Self-Evaluation Survey in Multiple İntelligence" developed by Gardner and adapted toTurkish and customized the validity and reliability of this survey by Saban was used as a data collection tool. "Anova Test" was used to determine the differences between intelligence scores, and "Tukey HSD Test" was used to define the different group. The data collected by using survey was analyzed by using Spss 21 for Windows package program. As a result of the this study, In contrast to students' social, physical, inherent and naturist intelligence, there is a significant difference between linguistic, visual and musical intelligence in favor of the female students and logical intelligence in favor of the males students. In addition linguistic intelligence of subjects was found significantly different according to their deparment variables. Logical, visual, physical, musical, social, inherent and naturist intelligence were found at the same level. School of Physical Education and Sports students were found significantly higher level of logical, visual, physical and naturist intelligence areas. Moreover, department of Sports Management students were showed higher level of linguistic, musical, social and inherent intelligence areas, in comparison to other School of Physical Education and Sports departments' students.